2014
DOI: 10.4314/jasem.v18i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Watermelon (<i>Citrullus lanatus</i>) Seed on Blood Glucose and Electrolyte Parameters in Diabetic Wistar Rats

Abstract: Given the prevalence of diabetes worldwide, with its associated complications,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
4
7
0
Order By: Relevance
“…On induction of diabetes, insulin was deficient leading to increased blood glucose level and entry of glucose into cells will be inefficient and hence cells are starved of glucose [24]. Treatment with aqueous extract of Citullus lanatus seeds showed a significant (p≤0.05) decreased in the plasma glucose levels in all the treated groups in a time and dose dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…On induction of diabetes, insulin was deficient leading to increased blood glucose level and entry of glucose into cells will be inefficient and hence cells are starved of glucose [24]. Treatment with aqueous extract of Citullus lanatus seeds showed a significant (p≤0.05) decreased in the plasma glucose levels in all the treated groups in a time and dose dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…In modern medicine, no satisfactory effective therapy is available to control DM along with electrolyte imbalance. The literature survey reveals that anti-diabetic herbs have the capacity to cure electrolyte imbalance along with DM [10][11][12][13]. In this regard, an herbal anti-diabetic drug used traditionally viz., momordica charantia and syzygium cumini were chosen for the present study to investigate a possible effect of the standardized aqueous fruit extract of momordica charantia (SAFEMC) and standardized aqueous seed extract of syzygium cumini (SASESC) on the serum electrolytes in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Citrullus lanatus (Watermelon) is the fruit of a plant originally from a vine of South Africa [17]. Studies have shown that it has the following properties: antioxidant [18,19], hypoglycemic [20], anti-inflammatory [21], vasodilatory [22], antihyperlipidemic and antidiabetic activities [23]. Thus the aim of this study was to evaluate the effects of Citrullus lanatus juice on fructoseinduced pup morphometric and metabolic changes in offspring of Wistar rats.…”
Section: Introductionmentioning
confidence: 99%